Optical Observation of Pool Boiling in Cooling Channels - FUCHINO, Shuichiro; NATORI, Naotake; ITO, Toshiaki; TAMADA, Noriharu (TEION KOGAKU (Journal of Cryogenics and Superconductivity Society of Japan), 1993)
In this paper, the phenomena of pool boiling and formation of flow convection in the cooling channels are observed by an optical method. The laser schlieren method with helium-neon laser of 7mW and a high speed camera with maximum shooting speed of 10, 000 frames per second are used to observe the fast phenomena. Analyzing films, transient formations of the flow convection have been observed. A bubble cluster with the thickness of around a hundred μm boundary layer has been formed during first 10ms and after that a turbulent layer has developed. The phenomena of the overshooting of the flow convection have been observed during heating. The flow velocity induced from the elapsing time till the overshooting becomes at maximum is almost equal to the predicted flow velocity calculated from the energy conservation law.